EXPERIMENTAL INSIGHTS ON THE GEOMETRY AND KINEMATICS OF FOLD-AND-THRUST BELTS ABOVE WEAK, VISCOUS EVAPORITIC DECOLLEMENT - Costa E.; Vendeville B.C. (My University, 2002)
This paper discusses the differences in mechanical properties and kinematics between fold-and-thrust belts detaching on evaporitic decollements and those detaching on stronger detachments. Physical experiments are described that model shortening of a thick brittle cover overlying a weak, viscous decollement to gain a better understanding of these differences. We tested the influence of (1) the decollement layer thickness and (2) the presence of a deformable backstop on the hinterland side and of a decollement pinch-out on the foreland side. Because of the very low shear strength of the viscous decollement, folds and thrusts did not propagate according to a piggy-back sequence but by centripetal, back-and-forth propagation. Additional shortening was accommodated by growth of all existing structures. Fold symmetry and thrust vergence varied between experiments. Models confined between two rigid, vertical endwalls always deformed by symmetric folding and thrusting. In models having a deformable backstop and a foreland decollement pinch-out, forethrusting initially dominated, folds were asymmetric, and fault blocks rotated. In models having a thick decollement layer, folds kept growing asymmetrically. Diapirism also depended on the initial decollement geometry. Diapirs formed only in models having a deformable backstop and were restricted to the hanging wall of a fault-related fold. Finally, the implications of such kinematics on the thermal history are discussed as well as the likelihood of hydrocarbon maturation and preservation.
Keywords: PHYSICAL MODELS; SALT TECTONICS; FOLD-AND-THRUST BELTS; KINEMATICS; GEOMETRY; DIAPIRISM